2022
DOI: 10.3390/fermentation8070301
|View full text |Cite
|
Sign up to set email alerts
|

Technoeconomic Evaluation of Microalgae Oil Production: Effect of Cell Disruption Method

Abstract: Microalgae have a high capacity to capture CO2. Additionally, biomass contains lipids that can be used to produce biofuels, biolubricants, and other compounds of commercial interest. This study analyzed various scenarios for microalgae lipid production by simulation. These scenarios include cultivation in raceway ponds, primary harvest with three flocculants, secondary harvest with pressure filter (and drying if necessary), and three different technologies for the cell disruption step, which facilitates lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…This stage represents only 0.5% of the total operating costs of the process, of which 1.6% is due to the consumption of fresh water for washing the biomass, 0.8% is due to energy consumption, 6.1% is for labor, and 91.5% is associated with the costs associated with the facilities, such as equipment maintenance, among others. This technology has been compared in the literature with centrifugation (a widely used technique), and it has been shown that filtration has lower operating costs and lower energy consumption, saving 25-90% of energy [36,37]. Finally, in the extraction stage, the wet biomass is mixed with the solvent and then the chlorophyll is separated using evaporation.…”
Section: Results Of the Techno-economic Evaluation Of The Production ...mentioning
confidence: 99%
“…This stage represents only 0.5% of the total operating costs of the process, of which 1.6% is due to the consumption of fresh water for washing the biomass, 0.8% is due to energy consumption, 6.1% is for labor, and 91.5% is associated with the costs associated with the facilities, such as equipment maintenance, among others. This technology has been compared in the literature with centrifugation (a widely used technique), and it has been shown that filtration has lower operating costs and lower energy consumption, saving 25-90% of energy [36,37]. Finally, in the extraction stage, the wet biomass is mixed with the solvent and then the chlorophyll is separated using evaporation.…”
Section: Results Of the Techno-economic Evaluation Of The Production ...mentioning
confidence: 99%
“…Thus, simultaneous CO 2 capture of industrial flue gas and wastewater treatment via microalgae recently have attracted increasing attention (Zhang et al, 2023b). CO 2 capture efficiency of 102.13 t/a was achieved through the cultivation of microalgae Chlorella vulgaris in a raceway pond (Valdovinos-García et al, 2020). In addition, the sulfur oxides (SO x ) and nitrogen oxide (NO x ) in the flue gas can be also removed by microalgae.…”
Section: Simultaneous Nitrate Recovery and Co 2 Reduction By Microalgaementioning
confidence: 99%
“…Life cycle inventory (LCI) data were obtained from the literature [22][23][24][25][26][27]. The input and output flow for each step of the process scope are shown in Table 1.…”
Section: Life Cycle Inventory (Lci)mentioning
confidence: 99%